Evaluation of two sequences of DNA barcodes in germplasms of Arracacia xanthorrhiza (Apiaceae) from Ecuador - Dávila, Marta (2019)
The present study aimed to evaluate the Arracacia xanthorrhiza rbcL chloroplast gene and the non-coding spacer region psbA-trnH as a possible barcode sequence. Plant material of A. xanthorrhiza was collected in orchards of Pichincha, Tungurahua and Cotopaxi provinces. This material were cultivated in standard conditions in the la Facultad de Ciencias Agropecuarias de la Universidad Técnica. The rbcL locus analysis identified the five materials of A. xanthorrhiza with between 97 and 99% homology. The sequence alignment of rbcL locus and psbA-trnH allowed to differentiate two groups, the first group with SJ, QU, PP and B, showing low diversity among them, while the second group consisted of the CH material grown in 3260 m of altitude. In the second tree, the divergence between the materials collected in different provinces of the Ecuadorian Sierra was demonstrated, separating them according to their locality, as well as the color of the root pulp The non-coding intergenic region (psbA-trnH) allowed identify and obtain the genetic diversity of cultivated materials of A. xanthorrhiza, from various geographical areas of the Ecuadorian Sierra, with distinctive morphological characteristics. Additionally, this sequence was able to differentiate A. xanthorrhiza from other species of the Apiaceae family, which is recommended as a bar code.